2021
DOI: 10.1148/radiol.2021210479
|View full text |Cite
|
Sign up to set email alerts
|

Central Retinal Artery Occlusion in Patients with COVID-19: Imaging for Underlying Causes

Abstract: on behalf of the SFNR's COVID study group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…HIV retinopathy will cause micro vascular changes that mimics diabetic retinopathy, CRAO in Z positive patients is very rare, usually large vessel involvement occurs in HIV patients associated with comorbidities but in these cases the co-existing COVID-19 may be responsible for the major vascular occlusions. COVID-19 systemic infection is prone to endothelial insult with vasculitis tendency, in which bilateral CRAO would not be unusual [15]. MRI of diffusion weighted images in patients with CRAO showed retinal hyper signal diffusion of the papilla or scattered diffusion restriction over the retina.…”
Section: Discussionmentioning
confidence: 98%
“…HIV retinopathy will cause micro vascular changes that mimics diabetic retinopathy, CRAO in Z positive patients is very rare, usually large vessel involvement occurs in HIV patients associated with comorbidities but in these cases the co-existing COVID-19 may be responsible for the major vascular occlusions. COVID-19 systemic infection is prone to endothelial insult with vasculitis tendency, in which bilateral CRAO would not be unusual [15]. MRI of diffusion weighted images in patients with CRAO showed retinal hyper signal diffusion of the papilla or scattered diffusion restriction over the retina.…”
Section: Discussionmentioning
confidence: 98%
“…COVID-19 is a condition that has been associated with thrombotic events and a hypercoagulable state. 5 , 6 There have been a few reports of Central Retinal Artery Occlusion (CRAO) and other retinal manifestations such as paracentral acute middle maculopathy (PAMM) associated with COVID-19, 1 , 7 10 but many of these were associated with severe COVID-19 infections. In our case, the patient suffered only very mild symptoms without being systemically unwell, yet still developed significant retinal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological examinations: To rule out orbital or intracranial pathologies, CT or cranial magnetic resonance imaging (MRI) can be initiated [61]. Although 90% of patients did not have neurological symptoms, Lauda et al found, in a retrospective MRI study of patients with CRAO (100 patients), BRAO (45 patients) and amaurosis fugax (68 patients), that 23% exhibited brain infarctions [62].…”
Section: Systemic Assessment and Management Of Retinal Artery Occlusionmentioning
confidence: 99%